Ghana : Poverty and Social Impact Analysis of Electricity Tariffs - Keener, Sarah; Ghosh Banerjee, Sudeshna (2014)
The World Bank's assistance was requested to conduct a Poverty and Social Impact Analysis assessing the direct and indirect impacts, as well as options for electricity pricing for the poor. Results of three different instruments (a small scale household survey focusing on consumer and social impact assessments of tariff changes, the analysis of a an existing nationally representative household survey and a stakeholder analysis) pointed to a rather high potential of the lifeline mechanism to protect the poor, but also showed that the knowledge of this subsidy and hence its coverage is much lower in rural areas. While the poor protecting mechanism seems quite effective, broader sector reforms threaten its sustainability (i.e., allowing larger customers to directly negotiate price conditions with the electricity company might increase the pressure on tariff adjustments for other customer groups, strain utility's finances and inhibit or slow connections of less profitable customers.